Walnut Oil Extract and Its Ability to Scavenge Free Radicals, Phenolic Content and Effective Antioxidants - Shemaa A. Ayob (Tikrit Journal of Pure Science, 2025)
Walnuts have been the oldest food for living things. It contains biologically active antioxidants, vitamin E, omega-3 fatty acids, moreover minerals such as sodium, calcium, iron, copper, magnesium and manganese, protein and fiber, etc making it a comprehensive healthy meal. This phenols in green walnut fruits have extracted in our study using methanol. Protocatechuic acid, sinapic acid, gallic acid, chlorogenic acid, and catechin have found among the individual and total phenols. Single-phenolic compound quantification is carried out using a SYKAMN chromatography system and reverse phase HPLC analysis. By using the Folin-Ciocâlteu technique, the total phenolic content (TPC) of the ethanolic extract has been calculated. The IC50 was measured, as well as the free radical scavenging of DPPH. The current research demonstrates the content of phenolic compounds in walnut oil found in the local markets of the city of Mosul, its activity as antioxidants, and its effectiveness in combating free radicals within the body when added to meals. This study may help clarify the overall health benefits of eating walnuts.